Hepatitis B reactivation in HBsAg‐negative/HBcAb‐positive patients receiving rituximab for lymphoma: a meta‐analysis. Issue 10 (13th March 2015) - Mozessohn, L.; Chan, K. K. W.; Feld, J. J.; Hicks, L. K.
Summary Patients with chronic hepatitis B (HBsAg‐positive) are at risk of viral reactivation if rituximab is administered without antiviral treatment, a potentially fatal complication of treatment. Patients with so‐called 'resolved hepatitis B virus infection' (HBsAg‐negative/cAb‐positive) may also be at risk. We performed a systematic review of the English and Chinese language literature to estimate the risk of hepatitis B virus (HBV) reactivation in HBsAg‐negative/cAb‐positive patients receiving rituximab for lymphoma. A pooled risk estimate was calculated for HBV reactivation. The impact of HBsAb status and study design on reactivation rates was explored. Data from 578 patients in 15 studies were included. 'Clinical HBV reactivation', (ALT >3 × normal and either an increase in HBV DNA from baseline or HBsAg seroreversion), was estimated at 6.3% (I2 = 63%, P = 0.006). Significant heterogeneity was detected. Reactivation rates were higher in prospective vs retrospective studies (14.2% vs 3.8%; OR = 4.39, 95% CI 0.83–23.28). Exploratory analyses found no effect of HBsAb status on reactivation risk (OR = 0.083; P = 0.151). Our meta‐analysis confirms a measurable and potentially substantial risk of HBV reactivation in HBsAg‐negative/cAb‐positive patients exposed to rituximab. However, heterogeneity in the existing literature limits the generalizability of our findings. Large, prospective studies, with uniform definitions of HBV reactivation, are needed to clarify the risk of HBV reactivation in HBsAg‐negative/cAb‐positive patients.